Affective Assessment within Madrasa Teachers: An Analysis of Iterative Thematic Inquiry - Zubaidah, Zubaidah; Suraiya, Suraiya; Manan, Abdul; Kamarullah, Kamarullah; Embong, Rahimah; Nurrahmi, Nurrahmi (SCAD Independent, 2026)
Effective assessment of students’ attitudes, behaviors, and values is a key component of value-based education reforms, yet its implementation often remains uneven at the classroom level. This study examines how affective assessment policies are enacted in madrasa education under the KDJPI framework in Aceh Province, Indonesia. Using a qualitative research design grounded in Iterative Thematic Inquiry, the study analyzes data from questionnaires administered to 224 madrasa teachers, semi-structured interviews with six teachers (E1–E6), and relevant instructional documents. The findings show that the persistent gap between affective assessment policy and practice cannot be sufficiently explained by teachers’ lack of commitment or competence. Although teachers generally demonstrate positive orientations toward affective assessment instruments such as reflective journaling and checklists, their implementation remains inconsistent due to structural constraints, including limited instructional time, large class sizes, administrative demands, and insufficient institutional support. In response, teachers adopt adaptive strategies that reflect professional agency but also reveal the limits of individual effort in the absence of coherent governance arrangements. By conceptualizing affective assessment as a negotiated and structurally constrained practice, this study contributes to debates on policy enactment and non-cognitive assessment in value-based education systems, with implications extending beyond the specific socio-religious context of Aceh.